Involvement of quinolinic acid in the neuropathogenesis of amyotrophic lateral sclerosis. (January 2017) - Lee, Jong-Min; Tan, Vanessa; Lovejoy, David; Braidy, Nady; Rowe, Dominic B.; Brew, Bruce J.; Guillemin, Gilles J.
Abstract: Amyotrophic lateral sclerosis (ALS) is the most common adult-onset motor neuron disease characterized by a progressive degeneration of central and peripheral motor neurons, leading to the atrophy of voluntary muscles. It has been previously demonstrated that the kynurenine pathway (KP), the major biochemical pathway for tryptophan metabolism, is dysregulated in ALS. In particular, the neuroactive intermediate, quinolinic acid (QUIN) has been shown to accumulate with a concomitant decrease in other neuroprotective and immunomodulatory KP metabolites. Furthermore, multiple biochemical phenomena associated with QUIN cytotoxicity are present in ALS, suggesting that QUIN may play a substantial role in the pathogenesis of ALS. This review highlights the potential roles of QUIN in ALS, and explores KP modulation as a therapeutic candidate in ALS. This article is part of the Special Issue entitled 'The Kynurenine Pathway in Health and Disease'. Highlights: This review describes the mechanisms involving the neurotoxin quinolinic acid in ALS. Highlights the overlap between QUIN toxicity and ALS mechanisms, and provides evidence for a correlation between QUIN and ALS. Summary of pharmacological drugs tested in ALS, and their potential correlation to KP and QUIN. Proposal of using KP modulating agents as potential ALS treatments to alter diseases phenotype.